Effects of inclination angle on natural convection in enclosures filled with Cu-water nanofluid - Abu-Nada, Eiyad; Öztop, Hakan Fehmi (Elsevier Science Inc, 2009)
Effects of inclination angle on natural convection heat transfer and fluid flow in a two-dimensional enclosure filled with Cu-nanofluid has been analyzed numerically. The performance of nanofluids is tested inside an enclosure by taking into account the solid particle dispersion. The angle of inclination is used as a control parameter for flow and heat transfer. It was varied from = 0 degrees to = 120 degrees. The governing equations are solved with finite-volume technique for the range of Rayleigh numbers as 10(3) <= Ra <= 10(5). It is found that the effect of nanoparticles concentration on Nusselt number is more pronounced at low volume fraction than at high volume fraction. Inclination angle can be a control parameter for nanofluid filled enclosure. Percentage of heat transfer enhancement using nanoparticles decreases for higher Rayleigh numbers. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Nanofluids; Enclosure; Natural convection; Inclination angle